Mothers' satisfaction with transcutaneous electrical nerve stimulation (TENS) in relieving post-episiotomy pain: A clinical trial study - Roonak Shahoei; Shahnaz Salavati Ghasemi; Neda Sheikh zakaryaee; Seyedeh Soma Zakariaee (Mashhad University of Medical Sciences, 2022)
Introduction: The goal of developing midwifery and maternal care is to create a safe delivery and increase maternal satisfaction from birth process. The present study was conducted aimed to evaluate mothers' satisfaction with transcutaneous electrical nerve stimulation (TENS) in relieving post-episiotomy pain.Methods: This randomized clinical trial was performed on 80 primiparous women referred to Sanandaj Besat Hospital in 2018. Patients were randomly divided into two groups: intervention (TENS-On) and placebo (TENS-Off) groups. TENS electrodes were located in the genitofemoral and pudendal nerves. The satisfaction from TENS was assessed by a researcher-made questionnaire. Data were analyzed using SPSS (version 20.0) and Pearson correlation, Independent t-test, Kruskal-Wallis, variance analysis, and Mann-Whitney tests. P<0.05 was considered statistically significant.Results: The intervention and placebo groups had a high level of satisfaction. However, the mean satisfaction in the intervention group (17.35±1.96) was significantly higher than the placebo group (13.45±2.02) (p<0.001). There was no significant relationship between demographic variable and satisfaction level (p˃0.05).Conclusion: TENS can have a noticeable effect on the level of maternal satisfaction. Therefore, it is suggested to implement TENS to reduce post-episiotomy pain in all maternity units in order to increase the level of satisfaction of patients and improve the level of mental health of mothers.